Relationships between Economic Growth and Population Health in Low and Middle Income Countries - Swint, J. Michael (2012)
From 1960 to the present, many low and middle income countries have experienced significant economic growth and unprecedented improvements in population health. We examine the complex relationship between economic growth and population health, including the economic and health impacts of malaria, tuberculosis, HIV/AIDS, malnutrition, reproductive health issues, and the associated intervention policies. We also examine the impact of several pertinent economic policies on population health, including microfinance, the TRIPS agreement, and UNIT AID, an international organization for purchasing drugs for use against AIDS, malaria, and tuberculosis. In addition we examine the effects of globalization on population health and economic growth. The evidence indicates that investment in improved population health is a reasonable macroeconomic policy tool for economic growth in low and middle income countries because improved health status has a positive impact on economic performance, and diminished health status has a negative impact on economic performance. Furthermore, variations in the rates of diffusion of disease control technologies have been a major cause of the variations in population health and economic growth between countries. Since 1960, low and middle income countries have been much more successful in closing the life expectancy gap than the economic development gap with high income OECD countries. Finally, while some progress has been made, achieving the infant and childhood mortality Millennium Development Goals will require a substantial investment in the increased diffusion of existing disease control knowledge and technology. Increased income per capita alone will not be sufficient.